RNA-Seq Analysis of Microglia Reveals Time-Dependent Activation of Specific Genetic Programs following Spinal Cord Injury - Noristani, Harun N.; Gerber, Yannick N.; Sabourin, Jean-Charles; Le Corre, Marine; Lonjon, Nicolas; Mestre-Frances, Nadine; Hirbec, Hélène E.; Perrin, Florence E. (Frontiers in Molecular Neuroscience, 2017)
Neurons have inherent competence to regrow following injury, although not spontaneously. Spinal cord injury (SCI) induces a pronounced neuroinflammation driven by resident microglia and infiltrating peripheral macrophages. Microglia are the first reactive glial population after SCI and participate in recruitment of monocytes-derived macrophages to the lesion site. Both positive and negative influence of microglia and macrophages on axonal regeneration had been reported after SCI, raising the issue whether their response depends on time post-lesion or different lesion severity. We analyzed molecular alterations in microglia at several time-points after different SCI severities using RNA-sequencing. We demonstrate that activation of microglia is time-dependent post-injury but is independent of lesion severity. Early transcriptomic response of microglia after SCI involves proliferation and neuroprotection, which is then switched to neuroinflammation at later stages. Moreover, SCI induces an autologous microglia expression of astrocytic markers with over 6% of microglia expressing glial fibrillary acidic protein and vimentin from as early as 72 hours post-lesion and up to 6 weeks after injury. We also identified the potential involvement of DNA damage and in particular tumour suppressor gene breast cancer susceptibility gene 1 (Brca1) in microglia after SCI. Finally, we established that BRCA1 protein is specifically expressed in non-human primate spinal microglia and is upregulated after SCI. Our data provide the first transcriptomic analysis of microglia at multiple stages after different SCI severities. Injury-induced microglia expression of astrocytic markers at RNA and protein levels demonstrates novel insights into microglia plasticity. Finally, increased microglia expression of BRCA1 in rodents and non-human primate model of SCI, suggests the involvement of oncogenic proteins after CNS lesion.